Perkembangan Pemikiran Fiqh Pada Masa Awal: Telaah atas Pemikiran Imam al-Shafi'i - Ajat Sudrajat (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to trace the development of fiqh thought in the early days of Islam through an examination of the intellectual contributions of Imam al-Shafi'i. As a central figure in the formation of the ushul fiqh system, al-Shafi'i is known for his work al-Risalah, which became the foundation for formulating the methodology of istinbath law. This study uses a qualitative method with a literature study approach, analyzing primary and secondary works that discuss the legal thought of Imam al-Shafi'i. The results show that al-Shafi'i succeeded in systematizing the sources of Islamic law, namely the Qur'an, sunnah, ijma', and qiyas, and rejecting legal practices that were not based on scripture. His thinking became an important turning point in the consolidation of fiqh from local practices to a standardized methodological framework. This study emphasizes that al-Shafi'i's thinking played a key role in the development of classical and modern Islamic law.